2019
DOI: 10.17159/2078-5151/2019/v57n4a2920
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of patients undergoing lower extremity amputation at RK Khan Hospital, Chatsworth

Abstract: Background: Amputation is one of the oldest and most commonly performed surgical procedures. Objective: To review the knowledge and attitude of patients undergoing lower extremity amputations and describe the associated causative factors. Methodology: A questionnaire-based prospective study assessing patients either preoperatively or immediately postoperatively regarding their knowledge and attitudes toward lower extremity amputation was conducted between November 2016 and April 2017. Extracted data was captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This finding corroborates the reports from previous quantitative studies on LLA knowledge amongst persons with DM in SA. 8 , 30 Studies have also shown the role of education and knowledge of DM disease process and foot care on health-seeking behaviour and improved health advocacy. 22 Knowledge of foot care and engaging in recommended foot examination reduce the risk for LLA.…”
Section: Discussionmentioning
confidence: 99%
“…This finding corroborates the reports from previous quantitative studies on LLA knowledge amongst persons with DM in SA. 8 , 30 Studies have also shown the role of education and knowledge of DM disease process and foot care on health-seeking behaviour and improved health advocacy. 22 Knowledge of foot care and engaging in recommended foot examination reduce the risk for LLA.…”
Section: Discussionmentioning
confidence: 99%